The nanny : [compact disc, unabridged] a novel - Macmillan, Gilly (Harper Collins Publishers, 2019)
When her beloved nanny, Hannah, left without a trace in the summer of 1988, seven-year-old Jocelyn Holt was devastated. Haunted by the loss, Jo grew up bitter and distant, and eventually left her parents and Lake Hall, their faded aristocratic home, behind. Thirty years later, Jo returns to the house and is forced to confront her troubled relationship with her mother. But when human remains are accidentally uncovered in a lake on the estate, Jo begins to question everything she thought she knew.